Glycogen Synthase Phosphatase Interacts with Heat Shock Factor To Activate CUP1 Gene Transcription in Saccharomyces cerevisiae - Lin, Janine T. (American Society for Microbiology, 1999)
Upon heat shock, transcription of many stress-inducible genes is rapidly and dramatically stimulated by heat shock factor (HSF). A central region of the yeast HSF (designated HSFrr for “repression region”) was previously identified and proposed to be involved in repressing the activation domain under non-heat-shock conditions. Here, we used the phage display system to isolate proteins that interact with HSFrr. This should identify factors that modulate HSF activity or directly participate in HSF-mediated transcriptional activation. We constructed a randomly sheared yeast genomic library to express yeast proteins on the surface of λ phage. HSFrr binding phages were selected by cycles of affinity chromatography. DNA sequencing identified an HSFrr-interacting phage that contains the GAC1 gene. The GAC1 gene encodes the regulatory subunit for a type 1 serine/threonine phosphoprotein phosphatase, Glc7. Both gac1 and glc7 mutations had little effect on HSF activation of gene transcription of two heat shock genes, SSA4 and HSP82. In contrast, heat shock induction of CUP1 gene expression was completely abolished in a glc7 mutant and reduced in a gac1 mutant. The results demonstrate that the Glc7 phosphatase and its Gac1 regulatory subunit play positive roles in HSF activation of CUP1 transcription.